The Effects of Dietary Interventions on Cardiovascular Indexes among Individuals with Cold and Hot Temperaments Based on Persian Medicine - Maryam Yavari; Hossein mozafarvandi; Kiyan Heshmat Ghahdarijani; Javad Shahabi; Maedeh Esmailzadeh; Samaneh Pourajam (Tehran University of Medical Sciences, 2024)
This study aimed to explore potential relationships between dietary patterns aligned with cold or hot temperaments and cardiovascular parameters among healthy individuals. This randomized clinical trial was conducted in 2020 with 65 healthy volunteers. Participants were categorized into two groups, specifically as hot or cold temperaments. In the initial phase, we measured body temperature, systolic and diastolic blood pressure, and conducted the Heart Rate Variability (HRV) test. Subsequently, participants received a three-day diet plan with a similar nature to their body temperament (second phase). The same measurements were repeated after three days. Following this, participants returned to a normal daily diet for three days. In the third phase, they received a diet plan of the opposite nature to their temperament for another three days, and the same battery of tests was conducted at the study's conclusion. In both the cold temperament group during the second phase and the hot temperament group during the third phase, mean body temperature, heart rate, systolic and diastolic blood pressure were significantly lower than in other phases (P < 0.05). Additionally, HRV indexes, including RMSSD, SDNNInd, and QT, were significantly higher during the second phase for the cold temperament group and the third phase for the hot temperament group compared to other phases (P < 0.05). Irrespective of individual body temperament, the consumption of a cold-natured diet led to a significant decrease in mean body temperature, heart rate, systolic and diastolic blood pressure. This effect may be attributed to the activation of the parasympathetic nervous system.